Peran Storytelling dalam Pengembangan Kecerdasan Emosional pada Mata Pelajaran Sejarah Kebudayaan Islam di MTs Babussalam Bengkulu Utara - Siti Sundari; Nurus Amzana; Emy Herawati (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to analyze and test the significance of the role and effectiveness of the Storytelling method in enhancing students' Emotional Intelligence (EQ) in the Islamic Cultural History (SKI) subject at MTs Babussalam Bengkulu Utara. Employing a quasi-experimental design with a quantitative approach, the research utilized a Non-Equivalent Control Group Design, involving an experimental group receiving Storytelling treatment and a control group using conventional methods. The population consisted of all eighth-grade students at MTs Babussalam Bengkulu Utara, with a sample of two classes (N=60, 30 students each) obtained through cluster random sampling or purposive sampling. Data were collected via Likert-scale questionnaires for pretest and posttest EQ measurements, supplemented by observation and documentation. Analysis employed inferential statistics, preceded by normality and homogeneity tests, and primary hypothesis testing used independent sample t-test or ANCOVA to compare posttest EQ score differences between groups (α=0.05). Results indicated a significant difference between the experimental group (mean 92.15) and control group (mean 83.40), with Sig. 2-tailed at 0.000 (0.000 < 0.05), demonstrating Storytelling's significant role in EQ development through internalization of exemplary values from SKI, particularly in empathy and self-management. Recommendation: SKI teachers at MTs Babussalam should adopt Storytelling as a primary strategy to bridge historical knowledge with affective character formation in students.